Biomechanical impact of C2 pedicle screw length in an atlantoaxial fusion construct - Xu, Risheng (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Posterior, atlantoaxial (AA) fusions of the cervical spine may include either standard (26 mm) or short (16 mm) C2 pedicle screws. This manuscript focused on an in vitro biomechanical comparison of standard versus short C2 pedicle screws to perform posterior C1-C2 AA fusions. METHODS: Twelve human cadaveric spines underwent C1 lateral mass screw and standard C2 pedicle screw (n = 6) versus short C2 pedicle screw (n = 6) fixation. Six additional controls were not instrumented. The peak torque, peak rotational interval, and peak stiffness of the constructs were analyzed to failure levels. RESULTS: The peak torque to construct failure was not statistically significantly different among the control spine (12.2 Nm), short pedicle fixation (15.5 Nm), or the standard pedicle fixation (11.6 Nm), P = 0.79. While the angle at the peak rotation statistically significantly differed between the control specimens (47.7° of relative motion) and the overall instrumented specimens (P < 0.001), the 20.7° of relative rotation in the short C2 pedicle screw specimens was not statistically significantly higher than the 13.7° of relative rotation in the standard C2 pedicle screw specimens (P = 0.39). Similarly, although the average stiffness was statistically significantly lower in control group (0.026 Nm/degree) versus the overall instrumented specimens (P = 0.001), the standard C2 pedicle screws (2.54 Nm/degree) did not differ from the short C2 pedicle screws CONCLUSIONS: Both standard and short C2 pedicle screws allow for equally rigid fixation of C1 lateral mass-C2 AA fusions. Usage of a short C2 pedicle screw may be an acceptable method of stabilization in carefully selected patient populations.